Membumikan Islam Humanis Melalui Karya Sastra: Studi Analisis Novel Bumi Cinta Karya Habiburrahman El Shirazy - Inten Mustika Kusumaningtias (Matan : Journal of Islam and Muslim Society, 2022)
Being rahmatan lil'alamin should be a necessity for Muslims because, in essence, Islam comes with mercy, blessings, and also salvation to the universe without exception. All humans have the right to receive equal and equal treatment. This is what should have happened as exemplified by the prophet in his daily life and traces of life. However, we are often negligent so that we only treat our fellow class, race, or religion well and have antipathy towards those who have different identities from us. This study aims to reveal the value of humanist Islam from the social relations of the Ayyas character in the novel Bumi Cinta by Habiburrahman El Shirazy. This research was conducted using a literature study with sources and data collection methods by taking library data, reading, taking notes, processing research materials, and analyzed descriptively. The results of this study indicate that there are values ​​of humanist Islamic education that are condensed into attitudes of 1) Tolerance of fixed prices, 2) Rejection of all acts of dehumanization, and 3) Caring as a reflection of human humanity.